BUAH MENGKUDU (Morinda citrifolia), KANDUNGAN DAN EFEKTIVITASNYA SEBAGAI ANTIHIPERTENSI: LITERATURE REVIEW - Wahyudi Wahyudi (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2022)
Background: Hypertension is one of a disease high prevalence in the world today, often called the silent killer because it generally does not cause symptoms in sufferers. This disease is characterized by increased contraction of blood vessels which increases blood pressure against the walls of blood vessels. Mengkudu (Morinda citrifolia) is one of the most widely grown plants in Indonesia which has effective antihypertensive properties. Previous studies have shown that mengkudu can lower blood pressure significantly compared to negative controls. The purpose of writing this article is to make a literature review that comprehensively discusses the effectiveness of mengkudu as an antihypertensive from previous studies that have been carried out. Methods: The writing of this article uses the literature review method on research articles found in the Google Scholar and Science Direct database using the keywords mengkudu, Morinda Citrifolia, hypertension and blood pressure. The criteria for the selected articles are articles published between 2000-2022 in both national and international journals. Literature review was conducted by comparing research methods, processing methods and the results obtained from each article. Results: The results of previous studies showed that mengkudu had a significant effect on reducing blood pressure. The decrease in blood pressure is related to the content of prexeronin (endothelial vasoactive), scopoletin (causing vasodilation) and xeronine (diuretic effect) contained in mengkudu which can lower blood pressure by different mechanisms. Conlusion: The content of mengkudu has the potential as an antihypertensive because it can significantly lower blood pressure.